AN ANALYSIS OF CODE-SWITCHING IN DANIEL MANANTA NETWORK YOUTUBE CHANNEL - Nadia Azira; Indah Tri Purwanti; Eliwarti Eliwarti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper investigates code-switching based on the types and functions in Daniel Mananta Network YouTube Channel while interacting with each other in informal situations. A qualitative approach was applied to the descriptive study in this paper. The data were gathered through a qualitative method by observing and transcribing the selected YouTube videos. The researcher transcribed, coded, analyzed, and classified the gathered data as the main instrument to determine the classifications and functions of code-switching. The study focused on the classifications and functions of code-switching used within Indonesian-based conversation. The sample of the study involved 10 video playlists of Daniel Tetangga Kamu on the Daniel Mananta Network YouTube Channel. The duration of the 10 videos is 12 hours and 53 minutes. The findings indicate that the Daniel Mananta Network YouTube Channel’s participants frequently used intra-sentential code-switching rather than inter-sentential code-switching, tag switching, and intra-word code-switching. In addition, the researcher also found a new phenomenon of code-switching that emerged where intra-sentential code-switching occurred within inter-sentential code-switching. The findings of the study are not only code-switching but also code-mixing, which is a reduplication that occurred due to the common usage in Indonesian speech. Subsequently, the most frequent function of code-switching used by the participants in the Daniel Mananta Network YouTube Channel is lexical need. Furthermore, the participants in Daniel Mananta Network YouTube Channel code-switch are not only from Indonesian to English but also from English to Indonesian in the Indonesian-based conversation.